Orobanche purpurea (Orobanchaceae) in Poland: current distribution, taxonomy, plant communities, and preferred hosts - Piwowarczyk, Renata (Biodiversity: Research and Conservation, 2012)
The paper presents the current distribution of Orobanche purpurea s. str. (excl. O. bohemica) in Poland, based on a critical revision of herbarium and literature data as well as results of my field research. Most of the records date back to the 19th or early 20th century and are now historical. Most of them lack also herbarium documentation. Since the 1950s the species has been found in 10 new localities, only partly documented by herbarium specimens. Currently it is present in only 4 localities, in valleys of the Lower Vistula and the Lower Oder (Odra) rivers and in the Silesian-Kraków Upland (Wyżyna alπsko-Krakowska). These are some of the northernmost sites known for the species, and the new data extend its continuous distribution range. A map of its distribution in Poland is included. The taxonomy, biology, and ecology of O.purpurea are also discussed.